Online Reservation Management System to Increase Transaction Efficiency at MOMENKITA Photo Studio - Firmansyah, Firmansyah; Rais Rahmat Razak, Muhammad; Sofyan, Wahyudi (Journal of Accounting and Finance Management, 2024)
“Momenkita Studio” is a small and medium-sized enterprise (SME) operating in the creative industry, specifically as a photo studio. It faces challenges with management that has not yet been optimized. Some noticeable obstacles include the lack of a structured customer record system, often complicated scheduling, and unclear monitoring of studio activities. This inefficient management can lead to schedule overlaps, neglect in record-keeping, and difficulties in tracking payment transactions. This study uses a qualitative method. Therefore, there is a need for a solution that can improve management efficiency. This research discusses the design and development of a web-based customer record application aimed at enhancing management efficiency at “Momenkita Studio” using the waterfall method. This process includes analysis, design, coding, testing, and support stages. The website is designed to simplify the processes of recording, scheduling, and monitoring studio activities, allowing users to focus on the creative aspects of their work.